2014
DOI: 10.1007/s00167-014-3418-2
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative laxity measurements using a navigation system in anatomical double-bundle posterior cruciate ligament reconstruction

Abstract: Therapeutic study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Some previous clinical studies have similarly investigated the PTT with gravity sag view before and after double-bundle PCLR using autogenous hamstring tendon grafts. Kimura et al 24 reported that the PTT was significantly reduced from 12.0 ± 1.7 mm preoperatively to 2.3 ± 1.8 mm at 2 years after surgery; in their study, both the AL and the PM grafts were fixed at 90° of knee flexion, applying a manual anterior tibial load, and a hard knee brace was worn for 6 months. Meanwhile, Deie et al 9 reported that the PTT was improved from 8 to 14.5 mm preoperatively to 2.6 mm at >10 years postoperatively.…”
Section: Discussionmentioning
confidence: 97%
“…Some previous clinical studies have similarly investigated the PTT with gravity sag view before and after double-bundle PCLR using autogenous hamstring tendon grafts. Kimura et al 24 reported that the PTT was significantly reduced from 12.0 ± 1.7 mm preoperatively to 2.3 ± 1.8 mm at 2 years after surgery; in their study, both the AL and the PM grafts were fixed at 90° of knee flexion, applying a manual anterior tibial load, and a hard knee brace was worn for 6 months. Meanwhile, Deie et al 9 reported that the PTT was improved from 8 to 14.5 mm preoperatively to 2.6 mm at >10 years postoperatively.…”
Section: Discussionmentioning
confidence: 97%
“…Overcorrection in the coronal plane is a well‐recognized reason for failure resulting in over loading of the contralateral compartment [46, 47]. In addition, studies have shown that the use of short narrow intramedullary guides cannot prevent misalignment in the three anatomical planes [19, 25]. Despite these concerns, some recent reports of the first series of UKA to treat degenerative knees have enthusiastically recommended the technique.…”
Section: Discussionmentioning
confidence: 99%
“…He identified the “reproducible” tissues, including epithelium (skin) and endothelium, the “stable” tissues, including mesenchyme (tendons and ligaments), that recover very well, and the “noble tissues” (muscles and nerves), which should not be damaged as they had limited ability to recover [35]. With this in mind, true less invasive surgery should involve not only shorter incisions but also the preservation of soft tissues and joint kinematics using new surgical tools and smaller implants, redefining it as tissue sparing surgery [11, 25].…”
Section: Introductionmentioning
confidence: 99%
“…Intraoperative computer navigation initially was used to ensure anatomic graft placement during ACL reconstruction but is also being used to study anterior tibial translation immediately pre‐ and post‐reconstruction [29]. Recently, Kimura et al [20] adapted this technology to PCL reconstruction noting 18.6 ± 2.6 mm of posterior tibial translation preoperatively. Although reported accuracy of this technology is to within 1 mm of translation and 1° of rotation, this method is highly invasive and limited to the operative setting [21].…”
Section: Discussionmentioning
confidence: 99%